Forms and Meanings of Expression Connotations in the Mapettuada Process of Bugis Traditional Marriage Traditions in Liliriaja District, Soppeng Regency - Nurfadillah Nurfadillah; Kembong Daeng; Andi Agussalim Agussalim AJ (Universitas Negeri Makassar, 2021)
Forms and Meanings of Expression Connotations in the Mapettuada Process of Bugis Traditional Marriage Traditions in Liliriaja District, Soppeng Regency. This study aims to describe the form and meaning of expressions in the mapettuada procession of the Bugis traditional marriage tradition in Liliriaja District, Soppeng Regency. This research is a qualitative descriptive study. The data of this research are in the form of mapettuada expressions in the traditional Bugis marriage tradition in Liliriaja District, Soppeng Regency. The data techniques used in this study were observation, interview, recording, and recording techniques. The results showed that: (1) the form of the expression contained in the mapettuada procession of the Bugis community in Liliriaja District, Soppeng Regency, is a form of assimellereng expression, namely mappoji expressions, these expressions can be seen from the opening stage to the closing stage. The statement of love from the prospective groom as a sign to make the prospective bride his life partner as evidenced by too many processes before the mappettuada is carried out. This statement is very humane as a manifestation of the love that arises even though it uses different expressions, and (2) the expression used in the procession of the Bugis community mapettuada in Liliriaja District, Soppeng Regency contains the meaning of the simplicity and humility of the speaker which shows in every expression spoken, both from the male family and the female side.